Workplace Radiation Monitoring and Analysis: A Single Institution Based Study (Bangladesh Journal of Nuclear Medicine, 2024)
Purpose:  The  primary objectives of this study were threefold: first, to  comprehensively  assess radiation  exposure  levels within  the  Nuclear  Medicine (NM) institution; second, to identify and address potential risks  associated with diagnostic and therapeutic  procedures; and third, to  establish strong control measures and emergency response  plans.  These  goals collectively aim to contribute to the creation of a  personalized  radiation protection program that addresses the unique issues provided by  NM applications. Materials and Methods: Radiation doses were computed over a six-month  period using survey meter data gathered three times each day.  Measurements were carried out in ionization chambers using radiation's  ionizing  properties. Continuous radiation surveys used digital survey  meters in  designated regions,  which  were  classified according to  dose  rates, with a focus on monitoring doses from radiopharmaceuticals such as  131I and 99mTc. Results:  Continuous radiation surveys over six months identified  maximum values in specific areas within the institution, such as the SPECT  room and therapy patient room, all below the allowable limit. This ensured  the safety of personnel and patients while maintaining ambient radiation  levels outside the institution consistently below the permissible limit. Conclusion:  This study  provided essential data for establishing a dose  reduction strategy in a clinical NM facility, confirming INMAS Bogura as  free from radiation-induced risks and emphasizing the importance of  continuous evaluation, adherence to regulations, and long-term monitoring  to ensure safe radiological working conditions.Bangladesh J. Nuclear Med. 27(1): 39-43, 2024